Wise leadership timeless wisdom from the ancient Chinese : the ancient Chinese teach the most profound leadership wisdom - Sheh, Seow Wah
This book was written based on the works of the Chinese classics that include the school of naturalism of Lao Zi (about 570 BC), Lie Zi (about 4th century BC), Zhuang Zi (369-286 BC) and Huai Nan Zi (about 2nd century BC), the school of humanism of Confucius (551-479 BC) and Mencius (372-289BC), the school of legalism of Xunzi (313-238 BC) and Han Fei Zi (280-233 BC), and finally the school of utilitarianism of Mozi (479-381 BC). The Ancient Chinese teach the most profound leadership wisdom. Wisdom is not just about intelligence or cleverness. Wisdom is an integration of intelligence with experience and an integration of science and philosophy. Wisdom comes from living, from making mistakes, from listening to others and learning from others. This concept of 'leadership by wisdom' is highly relevant in today's leadership study and development. The wisdom of a leader should embrace the virtues of benevolence and morality with deep insights and creativity in perspective. It is insufficient for a leader to be knowledgeable or intelligent yet far from wise. In today's context, many leaders at organizational, national and international levels are grossly lacking in the wisdom to lead others. Wisdom is still a deficit in many of our world leaders today. For thousands of years, the Chinese have been known to be adaptable whereby they can be found in all corners of the world, and found to be doing well. The greatest wisdom of the Chinese is "Adaptability". In the 21st century, China and the Chinese, as one of the oldest civilizations, will continue to play an active role in the world, not just in the case of economic activity but culturally as well. At the time that Chinese culture has truly integrated with world culture, China can be expected to play the role of spearheading and promoting a Universal Culture of the world.